INTERPRETATION OF LITERATURE ON THE FORMATION OF FUNCTIONAL LITERACY OF PRIMARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2025)
This article is devoted to the interpretation of literature on the formation of functional literacy of primary school students. Today, further development of the education sector, analysis of functional factors influencing the further growth of students' knowledge and skills, their mental abilities, is one of the urgent tasks facing this area. From this point of view, it is important to study the necessary measures to develop the functional literacy of primary school students and ensure its sustainable growth. A comparative analysis of pedagogical factors that are considered important in improving students' literacy is also important.